Cultural studies, production et économie morale - Hesmondhalgh, David; Morin, Céline (Réseaux, 2015)
Les approches issues des cultural studies ont insufflé à la recherche sur les productions médiatiques et culturelles une vigueur nouvelle et nécessaire. Cependant, il devient de plus en plus clair au fil des ans qu’elles rencontrent également de sérieuses limites. L’évaluation menée dans cet article repose sur une première partie dans laquelle nous explorons, en profitant du recul historique, la période d’opposition entre les cultural studies et l’économie politique des années 1990, en distinguant ce que nous appelons les modes théorique et populiste des cultural studies. Nous esquissons ensuite les trois « écoles » des approches cultural studies vis-à-vis de la production et de l’économie : cultural economy, production studies, et creative industries analysis. Selon nous, ces approches en cultural studies de la production et de l’industrie dans le domaine de la culture pêchent, tant dans leur mode populiste que dans leur mode théorique, par le manque d’attention portée à des problématiques fondamentales liées à la normativité dans les rapports entre la culture, les médias et l’économie. Dans les deux dernières parties, portant sur le tournant du cultural labour et le concept d’économie morale, nous suggèrerons des solutions pour une prise en compte plus explicite des problèmes de normativité, proposant ainsi une base éthique potentiellement plus rigoureuse pour l’étude de questions importantes dans le champ de la production culturelle. Nous appliquerons succinctement ce système au rapport problématique entre les biens culturels et le bien-être dans les sociétés modernes., ENG: Cultural studies approaches have provided a welcome reinvigoration of research on media and cultural production. But, as the years go by, it becomes clearer that they also suffer from important limitations. To provide a basis for the assessment in this article, the first section revisits the 1990s moment of ‘political economy versus cultural studies’ with the benefit of hindsight, distinguishing what I call the theoretical and populist modes of cultural studies. I then outline three ‘schools’ of cultural studies approaches to production and economy : cultural economy, production studies, and creative industries analysis. My argument is that, in both its theoretical and populist modes, these cultural studies approaches to production and industry in the realm of culture suffer from a lack of attention to fundamental normative issues regarding the relationship between culture, media and economy. In the final two sections, which discuss the turn to cultural labour and the concept of moral economy, I offer suggestions for how key normative issues might be addressed in a more explicit way, potentially offering a more rigorous ethical grounding for important questions regarding the realm of cultural production. I briefly apply this to the problematic relationship between cultural goods and well-being in modern societies.
Keywords: cultural production; cultural studies; industry; moral economy

Internet, une société contre l’État ? - Loveluck, Benjamin (Réseaux, 2015)
L’informatique en réseau a souvent été présentée comme un instrument favorisant l’auto-organisation de la société civile, à partir de modes alternatifs de distribution du pouvoir et de coordination des activités. L’histoire d’internet, abordée du point de vue de l’histoire des idées, montre que de telles propriétés ont donné lieu à la formation d’une véritable philosophie politique que nous avons appelée le libéralisme informationnel. Celle-ci a vu différents modèles d’économie politique s’affronter ; nous en présentons ici le mouvement général ainsi que les divergences internes. Nous terminons par un exposé de trois grandes formes de gouvernementalité qui en sont issues, et qui ouvrent à une critique de l’économie politique en régime numérique : la captation, la dissémination et l’auto-institution., Network computing has often been presented as an instrument promoting self-organization within civil society, through alternative modes of power distribution and coordination of activities. The history of the Internet, considered from the perspective of the history of ideas, shows that these properties have led to the formation of a genuine political philosophy that we have called informational liberalism. This article presents its overall movement and internal divisions, understood as alternative models of political economy. Finally, three main forms of governmentality stemming from this framework are identified, which pave the way for a critique of political economy in a digital regime : capturing, dissemination and self-institution.
Keywords: information society; informational liberalism; internet

The social economy of new rural reconstruction - Jia'en, Pan; Jie, Du (China Journal of Social Work, 2011)
This paper employs the concept of ‘social economy’ to reflect on the authors' experiences in rural reconstruction efforts in Mainland China, including work on peasant cooperatives and community-supported agriculture. In practice, the social and the economic can never be clearly separated. Economic problems, which may superficially appear to be independent, are in fact over-determined by all kinds of social and cultural factors, so a holistic perspective of ‘social economy’ is needed to re-embed the economic into its social context. Such a perspective can help expand the space of our practice and reflection thereon, in particular helping practitioners to understand the difficulties encountered in rural reconstruction.
Keywords: China; new rural reconstruction; perspective; social economy

Neoliberalism as a state-centric class project: The Italian case - Briziarelli, Marco (Continuum: Journal of Media & Cultural Studies, 2011)
This essay sheds light on the neoliberal aspects of the Italian political-economic system exemplified in the relationship between capital, state and media. The main argument is that the specific marriage between neoliberalism and neocorporatism that characterizes Italy reveals a distinctive characteristic of neoliberalism: a class project relying heavily on the state. As Polanyi has suggested through the concept of 'embeddedness', capitalism has consistently developed through the double movement of preaching the independence of the free market from the state and requiring the state's protectionist interventions. After describing this state-centric framework to interpret neoliberalism, in the second part of the paper, I consider the political-economic history of Italy's recent decades, paying particular attention to the media system. I will examine the 'communicative performance' of neoliberalism in Berlusconi's discourses and concrete political decisions taken in the name of neoliberalism. The articulated relationship between media and politics reveals the continuous attempts by the advocates of neoliberalism to seize the state, not to reduce its intervention but in fact to manipulate the market.
Keywords: Italy; economic indicators; essays; mass media audiences; neoliberalism; political economic analysis

Local Food: A Social Movement? - Starr, Amory (Cultural Studies/Critical Methodologies, 2010)
This article analyzes the development of “local food” institutions from a social movements perspective. Over the last decade, institutions that “shorten the links” between producer and consumer have developed through a diverse collaboration of many social sectors (farmers, agronomic experts, retailers, chefs, food writers, and several distinct consumer sectors). Some agronomists and rural sociologists critical of the globalization and industrialization of agriculture have recognized this development as heralding Polanyian “reembedding” of market exchanges in social relations. This article analyzes whether and how local food is a social movement, using new social movement theory as an analytic framework.
Keywords: community-based economics; local food; local foods; localism; organic food; organic foods; social change; social movements; social psychology

Economics and the Space of Modernity: - Escobar, Arturo (Cultural Studies, 2005)
This text was the original second chapter of the author's doctoral dissertation (Escobar 1987); this chapter was never included in the book that eventually grew from the dissertation (Escobar 1995). Although the chapter's contribution to debates on the economy are largely synthetic and certainly not original, the author wanted to publish it for a number of reasons. First, the alleged triumph of neo-liberal ideologies and the increase in depth and scope of market cultures at present make even more important the task of cultural analysis of economics and the economy. This paper was an effort in this direction, particularly to mapping the genealogies of what in the paper is called ‘the Western economy’. Second, there have been some recent claims that the cultural analysis of economics and the economy has hardly been broached. References to Polanyi's foundational role in this respect are, of course, de rigueur, but one only needs to point at the pioneering work of Stephen Gudeman since the 1980s to dispute this claim. Third, the same cultural analysis is experiencing a much needed surge, with several groups today fully engaged with it from various – some times overlapping – perspectives. Finally, the impetus for this piece also comes from the creative efforts by a number of social movements in the world – such as some of the autonomistas in Argentina – to go even beyond ‘rethinking’ the economy to propose that what is needed is a new invention altogether.
Keywords: anthropology of modernity; cultural studies; cultures of economy; economic history; economics; genealogy; modernity; resistance; social history; third world